1992
DOI: 10.1113/jphysiol.1992.sp019253
|View full text |Cite
|
Sign up to set email alerts
|

The giant cardiac membrane patch method: stimulation of outward Na(+)‐Ca2+ exchange current by MgATP.

Abstract: SUMMARY1. A giant patch method was used to study the stimulatory effect of cytoplasmic MgATP on outward Na+-Ca2+ exchange current in inside-out cardiac membrane patches (1-10 GQ seals with 14-24 jum pipette tip diameters) excised from guineapig, rabbit and mouse myocytes.2. To establish the validity of the method with respect to structure, bleb formation was examined with electron microscopy and with confocal fluorescence light microscopy. The blebs, which form as the sarcolemma detaches, excluded intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
121
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 48 publications
9
121
0
2
Order By: Relevance
“…Similarly, the Na+-K+ pump in red blood cells (Proverbio & Hoffman, 1977) and in pancreatic fl-cells (Niki, Ashcroft & Ashcroft, 1989) (Allen & Orchard, 1986). A low affinity of the exchanger for ATPi would be similar to that reported recently for the ATPi sensitivity of the cardiac Na'-Ca2" exchanger by Hilgemann and co-workers (Collins, Somlyo & Hilgemann, 1992 Allen et al 1985). A role here for Pi seems unlikely, however, since it rises considerably during CN-application but not during DOG application (Allen et al 1985) Counillon & Pouysseger, 1993) has so far been shown not to be modulated by cAMPi to the extent that it is not directly phosphorylated by cAMP-dependent kinase (Fliegel et al 1992).…”
Section: Effect Of Cn-upon Flimentioning
confidence: 54%
“…Similarly, the Na+-K+ pump in red blood cells (Proverbio & Hoffman, 1977) and in pancreatic fl-cells (Niki, Ashcroft & Ashcroft, 1989) (Allen & Orchard, 1986). A low affinity of the exchanger for ATPi would be similar to that reported recently for the ATPi sensitivity of the cardiac Na'-Ca2" exchanger by Hilgemann and co-workers (Collins, Somlyo & Hilgemann, 1992 Allen et al 1985). A role here for Pi seems unlikely, however, since it rises considerably during CN-application but not during DOG application (Allen et al 1985) Counillon & Pouysseger, 1993) has so far been shown not to be modulated by cAMPi to the extent that it is not directly phosphorylated by cAMP-dependent kinase (Fliegel et al 1992).…”
Section: Effect Of Cn-upon Flimentioning
confidence: 54%
“…5). It should also be pointed out that MgATP-dependent stimulation of the cardiac NCX1 activity under patch conditions was suggested not to involve protein kinases (15), as briefly discussed in the Introduction. One possibility compatible with both the present and this previous result could be that phosphorylation of an unidentified ancillary factor(s) missing from the excised membrane patches, but not the direct phosphorylation of the NCX1 protein, is required for the PKC-dependent regulation of the NCX1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…of Molecular Physiology, National Cardiovascular Center Research Institute, Fujishiro-dai 5, Suita, Osaka 565, Japan. hanced by protein phosphatase inhibitor okadaic acid (15), suggesting no direct effect of ATP or involvement of protein kinases. Consistent with these findings is a recent report that phosphorylation of cardiac NCX1 isoform was not detected in 32 P-labeled Chinese hamster ovary or COS cells that stably expressed the bovine cardiac NCX1 (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect would occur in parallel with other factors that modulate NCX during changes in metabolism. For example, ATP depletion causes a significant decrease in cardiac NCX activity (19,20,30,31), and lactate accumulation not only increases cytosolic NADH but also mediates acidosis. Decreased pH inhibits NCX activity (32), which is fully reversible after pH normalization (33).…”
Section: Discussionmentioning
confidence: 99%